Fall in the Indian population after the arrival of the Spaniards. Diseases or exploitation? - Moreno Okuno, Alejandro Tatsuo; Ventosa-Santalària, Daniel (Investigación Económica, 2011)
In 1492, the same year that Christopher Columbus discovered America, the last Muslim stronghold in Spain was taken. Spain emerged then as the most important defender of the catholic faith in the world. At the same time, because of the continuous military campaigns, the Spanish Crown had an immense economic deficit (Díaz López 1994:25). In these circumstances, the discovery, conquest and colonization of America helped to attain a double goal, to fight for the Catholic religion and to obtain new financial resources.